Testing the potential mechanisms for the maintenance of a genetic color polymorphism in bluefin killifish populations - Johnson, Ashley M (Curr Zool, 2018)
The maintenance of genetic variation in the face of natural selection is a long-standing question in evolutionary biology. In the bluefin killifish Lucania goodei, male coloration is polymorphic. Males can produce either red or yellow coloration in their anal fins, and both color morphs are present in all springs. These 2 morphs are heritable and how they are maintained in nature is unknown. Here, we tested 2 mechanisms for the maintenance of the red/yellow color morphs. Negative frequency-dependent mating success predicts that rare males have a mating advantage over common males. Spatial variation in fitness predicts that different color morphs have an advantage in different microhabitat types. Using a breeding experiment, we tested these hypotheses by creating populations with different ratios of red to yellow males (5 red:1 yellow; 1 red:5 yellow) and determining male mating success on shallow and deep spawning substrates. We found no evidence of negative frequency-dependent mating success. Common morphs tended to have higher mating success, and this was particularly so on shallow spawning substrates. However, on deep substrates, red males enjoyed higher mating success than yellow males, particularly so when red males were rare. However, yellow males did not have an advantage at either depth nor when rare. We suggest that preference for red males is expressed in deeper water, possibly due to alterations in the lighting environment. Finally, male pigment levels were correlated with one another and predicted male mating success. Hence, pigmentation plays an important role in male mating success.